Canada's cannabis legalization and drivers' traffic-injury presentations to emergency departments in Ontario and Alberta, 2015-2019. (1st November 2021) - Callaghan, Russell C.; Sanches, Marcos; Vander Heiden, Julia; Asbridge, Mark; Stockwell, Tim; Macdonald, Scott; Peterman, Bronwen Hughes; Kish, Stephen J.
Highlights: Canada implemented cannabis legalization via the Cannabis Act on October 17, 2018. Legalization has raised concerns about increased traffic harms, especially among youth. ICD-10 drivers' traffic-injuries from all Ontario and Alberta emergency departments. Time Series analyses of weekly provincial counts of drivers' traffic injuries, 2015–2019. Legalization not associated with changes in traffic injuries in all drivers or youth drivers. Abstract: Background: Worldwide momentum toward legalization of recreational cannabis use has raised a common concern that such policies might increase cannabis-impaired driving and consequent traffic-related harms, especially among youth. The current study evaluated this issue in Canada. Methods: Utilizing provincial emergency department (ED) records (April 1, 2015-December 31, 2019) from Alberta and Ontario, Canada, we employed Seasonal Autoregressive Integrated Moving Average (SARIMA) models to assess associations between Canada's cannabis legalization (via the Cannabis Act implemented on October 17, 2018) and weekly provincial counts of ICD-10-CA-defined traffic-injury ED presentations. For each province (Alberta/Ontario), SARIMA models were developed on two driver groups: all drivers, and youth drivers (aged 14–17 years in Alberta; 16–18 years, Ontario). Results: There was no evidence of significant changes associated with cannabis legalization on post-legalization weekly counts of drivers' traffic-injury ED visits in: (1) Alberta, all drivers ( n = 52, 752 traffic-injury presentations), an increase of 9.17 visits (95 % CI -18.85; 37.20; p = 0.52); (2) Alberta, youth drivers ( n = 3265 presentations), a decrease of 0.66 visits (95 % CI -2.26; 0.94; p = 0.42); (3) Ontario, all drivers ( n = 186, 921 presentations), an increase of 28.93 visits (95 % CI -26.32; 84.19; p = 0.30); and (4) Ontario, youth drivers ( n = 4565), an increase of 0.09 visits (95 % CI -6.25; 6.42; p = 0.98). Conclusions: Implementation of the Cannabis Act was not associated with evidence of significant post-legalization changes in traffic-injury ED visits in Ontario or Alberta among all drivers or youth drivers, in particular.